Research and progress of microRNA-136 in metastatic tumors - Chenwen Wang; Zixiong Chen; Wei Ni; Jiang Wang; Wei Zhou (Frontiers in Oncology)
BackgroundMiR-136 is abnormally expressed in many types of metastatic tumors and is closely associated with tumor cell proliferation, apoptosis, invasion, and metastasis, indicating its important role in tumor development and progression. This review summarizes current knowledge regarding miR-136’s molecular mechanisms, functional roles, and impact on chemotherapy in different human cancers.MethodsA literature search was conducted in PubMed and Web of Science using “miR-136” and “metastatic tumors” as English keywords, and in CNKI and Wanfang databases using the same terms in Chinese. Studies related to miR-136 research in metastatic tumors and high-quality evidence from similar studies were included. Meta-analyses, dissertations, conference papers, low-quality articles, unavailable full-text articles, and republished articles were excluded.ResultsThis review synthesizes the current understanding of miR-136’s role in various cancers, including osteosarcoma, gastric cancer, gallbladder cancer, esophageal cancer, prostate cancer, colorectal cancer, breast cancer, glioma, and thyroid cancer. miR-136 acts as a tumor suppressor by targeting various genes, including MTDH, PTEN, MAP2K4, MUC1, LRH-1, MIEN1, RASAL2, CYR61, and KLF7. It influences multiple signaling pathways, including the ERK/mitogen-activated protein kinase, Wnt/β-catenin, Ha-Ras, PI3K/Akt, Aurora-A kinase, nuclear factor-κB, and JNK pathways. Furthermore, miR-136 is involved in chemoresistance by modulating ROCK1, PPP2R2A, and the miR-136-Notch3 signaling axis.ConclusionsMiR-136 demonstrates promising potential as a novel biomarker and therapeutic target in various human cancers. Further research is needed to fully elucidate its complex roles in cancer development, progression, and drug resistance, particularly regarding its potential in immunotherapy.